THU0513 Neonatal manifestations of immune-mediated rheumatic diseases: a retrospective longitudinal study in a tertiary hospital. (15th June 2017) - Bernardo, J; Brito, I; Guimarães, H; Guimarães, M; Fonseca, R
Abstract : Background: Autoimmune rheumatic diseases such as systemic lupus erythematosus (SLE), antiphospholipid antibody syndrome (APS) and Sjögren's syndrome (SS) are part of a clinical spectrum eligible to affect women in child-bearing ages, affecting neonatal outcomes. Cardiac, cutaneous, haematological, hepatic complications and, more rarely, pulmonary complications have been described. Objectives: This project aims to describe the occurrence of neonatal lupus manifestations and possible associated clinical factors among women with immune-mediated rheumatic diseases. Methods: A retrospective longitudinal study was performed including pregnant women with immune-mediated rheumatic diseases seen in a multidisciplinary group for autoimmune diseases during pregnancy between January 2010 and December 2015. Clinical and demographic data as well as and pregnancy outcomes and neonatal manifestations were collected through consultation of clinical files. Patients with and without neonatal lupus were compared using Mann-Whitney, qui-square and fisher tests (SPSS 24.0). Significance level was set as <0.05. Results: We included 151 gestations from a total of 140 women with a mean age of 32, 5±4, 4 years; 4 gestations were twin pregnancies. Within these 151 gestations, 54 (35, 8%) women had SLE, 17 (11, 3%) had Sjögren's syndrome, 17 (11, 3%) had rheumatoid arthritis, 41 had APS (27, 2%), 11 (7, 3%) had Behçet's disease, 4 (2, 6%) had systemic sclerosis, 8 (5, 3%) had mixed connective tissue disease and 16 (10, 6%) had other immune-mediated diseases. 35 (23, 2%) had anti-SSA/La antibodies, 18 (11, 9%) had anti-SSB antibodies, 6 (4, 0%) had anti-URNP antibodies and 43 (28, 5%) had anti-nuclear antibodies. During follow-up, 142 (94, 0%) babies were born and 7 (4, 6%) abortions and 2 (1, 3%) foetal losses occurred. 6 (4, 2%) neonates were born with neonatal lupus and 1 (0, 7%) died in uterus with a complete heart block. Out of the 6 babies with manifestations, 4 (66, 7%) were cardiac, 2 (33, 3%) were cutaneous, 1 (16, 7%) was hepatic, 2 (33, 3%) were haematological and 1 (16, 7%) was pulmonary. Neonatal lupus manifestations occurred more frequently in mothers with SS (23.5% vs 2.2%; p=0.003), anti-SSa/Ro (20% vs 0%; p<0.001), and anti-SSb/La (27.7% vs 1.5%; p<0.001). Conclusions: Our study proved a link between immune-mediated rheumatic diseases and specific neonatal outcomes. Disclosure of Interest: None declared